Lithium slag-based composite admixture and preparation method thereof

By reacting lithium slag with ammonium salts to generate SO42-, and combining it with desulfurizing agents and alkali treatment agents, lithium slag-based composite admixtures are prepared, solving the problem of limited lithium slag dosage in concrete and realizing the efficient utilization and environmentally friendly resource conversion of lithium slag.

CN119591335APending Publication Date: 2025-03-11JIANGXI JIULING LITHIUM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411102385.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The amount of lithium slag used in concrete admixtures is limited, making it difficult to utilize effectively and hindering the development of the lithium battery industry chain.

Method used

By reacting lithium slag with ammonium salt solution to generate SO42-, using a desulfurizing agent to reduce the sulfur content, and reacting it with an alkali treatment agent to generate beneficial cementitious materials, lithium slag-based composite admixtures are prepared by combining grinding and activator.

Benefits of technology

This increases the amount of lithium slag in concrete, enabling resource utilization, high performance, and harmless treatment, while enhancing the adhesion and strength of concrete and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591335A_ABST
    Figure CN119591335A_ABST
Patent Text Reader

Abstract

The invention provides a lithium slag-based composite admixture and a preparation method thereof, and in the preparation method of the lithium slag-based composite admixture, lithium slag is subjected to sulfur reduction, alkali treatment and grinding treatment, so that the sulfur content in the lithium slag is reduced, later hydration is promoted, and the doping amount of the lithium slag during preparation of the composite admixture is increased. According to the application, before the sulfur removal agent is added, the gypsum in the ammonium salt is utilized to react to generate SO4 < 2->, so that sulfur, which is originally insoluble in water, in the gypsum exists in a form which is easier to treat, and the sulfur reduction effect is improved. And the sulfur-reduced lithium slag and carbonate are subjected to a heating reaction, so that feldspar minerals in the lithium slag are subjected to bond breaking-dissociation, and a product beneficial to hydration of a cementing material is generated. And the pretreated lithium slag is cooperated with one or more industrial solid wastes to prepare the composite admixture, so that the recycling, high-performance and harmless utilization of the lithium slag is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste recycling, and in particular to a lithium slag-based composite admixture and a preparation method thereof. Background Art

[0002] Lithium slag is an industrial solid waste generated during the extraction of lithium from lithium ore. Most of the lithium slag is treated by stockpiling. The high sulfur content of lithium slag restricts the development of the lithium battery industry chain. At present, the amount of lithium slag added to concrete admixtures is limited due to the characteristics of lithium slag. Summary of the invention

[0003] The present application provides a lithium slag-based composite admixture and a preparation method thereof that are beneficial for increasing the lithium slag dosage.

[0004] In a first aspect, an embodiment of the present application provides a method for preparing a lithium slag-based composite admixture, the method comprising:

[0005] Mixing lithium slag with water, adding 5% to 8% ammonium salt solution, and separating after sufficient reaction to obtain pre-treated lithium slag and primary filtrate;

[0006] Adding a desulfurizing agent to the primary filtrate, mixing and stirring, and separating to obtain a secondary filtrate;

[0007] mixing the secondary filtrate with the pretreated lithium slag to form a mixed liquid;

[0008] Add 5% to 8% ammonium salt solution to the mixed solution, separate and obtain sulfur-reduced lithium slag after sufficient reaction;

[0009] The sulfur reduction filter residue and the alkali treatment agent are uniformly mixed and calcined for a preset time to obtain dry lithium slag;

[0010] The lithium slag, slag and fly ash are ground and dried, and the ground dry lithium slag, slag and fly ash are mixed with an activator in a preset ratio to obtain a lithium slag-based composite admixture.

[0011] According to the first aspect, in a possible implementation, the step of adding 5% to 8% ammonium salt solution to the mixed solution and separating to obtain sulfur-reduced lithium slag after sufficient reaction comprises:

[0012] The steps of adding 5% to 8% ammonium salt solution to the mixed solution, and separating to obtain pretreated lithium slag and primary filtrate after sufficient reaction; and repeating the steps of adding desulfurizing agent to the primary filtrate, mixing and stirring, and separating to obtain secondary filtrate 2-5 times; mixing the secondary filtrate with the pretreated lithium slag to form a mixed solution; and adding 5% to 8% ammonium salt solution to the mixed solution;

[0013] After sufficient reaction, the sulfur-reduced lithium slag is separated.

[0014] According to the first aspect, in a possible implementation manner, in the lithium slag-based composite admixture, the mass percentage content of the dry lithium slag is 35% to 50%.

[0015] According to the first aspect, in a possible implementation, the desulfurizing agent includes at least one of hydrotalcite, chitosan, and polyaluminium chloride.

[0016] According to the first aspect, in a possible implementation manner, the alkali treatment agent includes sodium carbonate, calcium carbonate or a mixture thereof.

[0017] According to the first aspect, in a possible implementation manner, the ammonium salt solution is a solution of one or more mixtures of ammonium carbonate, ammonium bicarbonate, and ammonium chloride.

[0018] According to the first aspect, in a possible implementation, in the step of uniformly mixing the sulfur reduction filter residue with the alkali treatment agent and calcining for a preset time, the calcination temperature is 750° C. to 850° C., and the calcination time is 1 to 3 hours.

[0019] According to the first aspect, in a possible implementation, the specific surface area of ​​the dry lithium slag after grinding is 450-550m2 / kg; the specific surface area of ​​the slag after grinding is 450-550m2 / kg, and the specific surface area of ​​the fly ash after grinding is 300-450m2 / kg.

[0020] According to the first aspect, in a possible implementation manner, the activator is one or more of silica fume, sodium metasilicate, sodium silicate, and sodium hexametaphosphate.

[0021] In a second aspect, an embodiment of the present application further provides a lithium slag-based composite admixture, wherein the lithium slag-based composite admixture is prepared by the preparation method of the lithium slag-based composite admixture described in the first aspect.

[0022] The lithium slag-based composite admixture and its preparation method provided in the present application, firstly, the lithium slag reacts with ammonium salt to change the properties of certain components in the lithium slag, especially the gypsum (mainly sulfur-containing component) therein, the ammonium salt reacts with the gypsum to generate SO4 2- , which makes the sulfur in the gypsum, which is originally insoluble in water, exist in a form that is easier to handle, and the sulfur reduction effect is achieved after the sulfur reduction agent is added; then, the sulfur-reducing lithium slag is heated to react with carbonate to break the bonds of the feldspar minerals in the lithium slag and dissociate to generate products that are beneficial to the hydration of the cementitious material; finally, the pretreated lithium slag is ground and mixed with one or more other industrial solid wastes to prepare a composite admixture, thereby realizing the resource utilization, high performance and harmless utilization of the lithium slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 It is a flowchart of a method for preparing a lithium slag-based composite admixture according to an embodiment of the present application;

[0025] Figure 2 It is a schematic flow chart of a method for preparing a lithium slag-based composite admixture according to another embodiment of the present application;. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0027] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0028] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0029] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0030] In a first aspect, the present application provides a method for preparing a lithium slag-based composite admixture, such as Figure 1 As shown, the method includes:

[0031] Step S10, mixing lithium slag with water, and adding 5% to 8% ammonium salt solution, and separating to obtain pretreated lithium slag and primary filtrate after sufficient reaction;

[0032] The lithium slag is mixed with water in a certain proportion to ensure that the lithium slag can be fully wetted and dispersed so that the subsequent reaction can proceed evenly.

[0033] Add 5% to 8% ammonium salt solution to the mixed solution. The ammonium salt solution can be a solution of one or more mixtures of ammonium carbonate, ammonium bicarbonate, and ammonium chloride. The specific choice of ammonium salt, the amount used, and the reaction time need to be adjusted according to the chemical composition of the lithium slag and the expected reaction effect to achieve the best pretreatment effect.

[0034] After adding the ammonium salt solution, stir it thoroughly to ensure that the ammonium salt and the components in the lithium slag can fully contact and react. The stirring time should be long enough to ensure that the reaction can proceed fully and achieve the desired pretreatment effect. After the reaction is completed, the solid and liquid in the mixed solution are separated by filtering or centrifugation.

[0035] After the reaction is completed, the solid and liquid in the mixed solution are separated by filtration or centrifugation. The separated solid is the pre-treated lithium slag, which will be used in the subsequent desulfurization and alkali treatment steps. The separated liquid is the primary filtrate, which can be further processed or recycled as needed.

[0036] Because the sulfur in lithium slag mainly exists in the form of gypsum, which is difficult to dissolve in water; after adding ammonium salt solution, gypsum will react with ammonium salt to generate SO4 2- , reducing the sulfur content in lithium slag, the separated primary filtrate contains the generated SO4 2- , which can be further processed as needed, such as recovering sulfate or performing other chemical treatments.

[0037] Step S20, adding a desulfurizing agent to the primary filtrate, mixing and stirring, and separating to obtain a secondary filtrate;

[0038] Add desulfurizer to the primary filtrate. The desulfurizer is used as an anion exchanger. Its anion exchange capacity is related to the type of anions between its layers. The order of anion exchange capacity of desulfurizer is CO3 2- >SO4 2- >HPO4 - >F - >Cl -> B(OH)4 - >NO 3- , which means that the desulfurizer can preferentially exchange sulfate ions in the filtrate.

[0039] After adding the desulfurizer, sufficient mixing and stirring is performed to ensure that the desulfurizer and the sulfate ions in the filtrate can fully contact and react.

[0040] In this application, an ammonium salt solution is first used to react with lithium slag to change the properties of certain components in the lithium slag, especially gypsum (mainly sulfur-containing component). The reaction of ammonium salt and gypsum generates SO4 2- , which allows the sulfur in the gypsum, which is originally difficult to dissolve in water, to exist in a form that is easier to handle, thereby improving the efficiency of the desulfurization step.

[0041] After the reaction is completed, the solid and liquid in the mixed solution are separated by filtration or centrifugation. The separated liquid is the secondary filtrate, in which the content of sulfate ions has been reduced.

[0042] The desulfurizer can be selected from one or more of hydrotalcite, chitosan, and polyaluminium chloride. These desulfurizers not only have excellent anion exchange capacity, but also have good adsorption capacity; by adding 0.1-1% of the desulfurizer to the primary filtrate, the sulfate ions in the filtrate can be effectively removed while adsorbing heavy metal ions.

[0043] Step S30, mixing the secondary filtrate with the pretreated lithium slag to form a mixed solution;

[0044] Step S40, adding 5% to 8% ammonium salt solution to the mixed solution, and separating to obtain sulfur-reduced lithium slag after sufficient reaction;

[0045] The secondary filtrate obtained in step S20 is mixed with the pretreated lithium slag obtained in step S10 to form a mixed solution. 5% to 8% ammonium salt solution is added to the mixed solution. The ammonium salt solution is added to react with the sulfur component in the mixed solution to further reduce the sulfur content in the lithium slag. After sufficient reaction, the solid and liquid in the mixed solution are separated by filtering or centrifugation. The separated solid is the sulfur-reduced lithium slag, in which the sulfur content has been significantly reduced, providing more favorable conditions for subsequent processing and utilization.

[0046] It is understandable that the above steps (i.e., adding ammonium salt solution to the mixed solution and separating to obtain sulfur-reduced lithium slag after reaction) can be repeated to further reduce the sulfur content in the lithium slag. Figure 2 As shown, when the steps are repeated, the sulfur reduction lithium slag obtained in the previous step can be regarded as a new "pre-treated lithium slag", and it can be mixed with the primary filtrate or the secondary filtrate obtained in the corresponding step to form a new mixed solution. Then, the ammonium salt solution is added to the new mixed solution again, and the sulfur reduction lithium slag with a lower sulfur content is separated. The number of times the sulfur reduction step is repeated can be determined according to actual needs, and it can usually be repeated 2 to 5 times to achieve the desired sulfur reduction effect.

[0047] Step S50, mixing the sulfur reduction filter residue and the alkali treatment agent uniformly and calcining for a preset time to obtain dry lithium slag;

[0048] The sulfur-reduced lithium slag obtained in step S40 is mixed evenly with an alkali treatment agent. The alkali treatment agent is a 2-5% carbonate solution, specifically an aqueous solution of sodium carbonate, calcium carbonate or a mixture thereof. The purpose of this step is to fully contact the sulfur-reduced lithium slag with the alkali treatment agent to prepare for subsequent reactions.

[0049] The uniformly mixed sulfur-reduced lithium slag and the alkali treatment agent are calcined at a temperature of 750° C. to 850° C. The calcination time is 1 to 3 hours to ensure that a sufficient chemical reaction occurs.

[0050] Under calcination conditions at 750-850°C, the sulfur-reduced lithium slag reacts with carbonates during heating, causing the feldspar minerals in the lithium slag to break bonds and dissociate, generating metaaluminates, metasilicates and other substances, thereby transforming the alkaline substances in the lithium slag for reuse. At the same time, these substances can react under the alkaline conditions of cement hydration to generate substances with bonding ability, thereby enhancing the adhesion and strength of the concrete.

[0051] Step S60, grinding dry lithium slag, slag and fly ash, and uniformly mixing the ground dry lithium slag, slag and fly ash with an activator in a preset ratio to obtain a lithium slag-based composite admixture.

[0052] The dried lithium slag obtained in step S50 is subjected to a grinding process and ground to a predetermined fineness by a professional grinding device to ensure its uniformity in subsequent mixing and reaction.

[0053] At the same time, slag and fly ash are also ground, using the same or similar grinding equipment to ensure that the particle size of all raw materials is uniform.

[0054] The powder can be processed by mechanical grinding machine, air flow grinding machine, grinding machine, etc. The powder formed by grinding can be sieved to ensure that the particle size of lithium slag, slag and fly ash powder is uniform.

[0055] The specific surface area of ​​dry lithium slag after grinding should be strictly controlled within the range of 450-550m2 / kg, the specific surface area of ​​slag should also be controlled within the range of 450-550m2 / kg, and the specific surface area of ​​fly ash should be controlled within the range of 300-450m2 / kg.

[0056] During the grinding process, due to the mechanical force, the molecular bonds of lithium slag will be broken and reorganized. This change can significantly improve the activity of lithium mica slag, so that it can better participate in chemical reactions in subsequent applications. That is, after the grinding process, the activity of lithium slag is improved, and it can more fully participate in the hydration reaction in concrete, play a better bonding role, and thus enhance the strength and durability of concrete.

[0057] According to the preset ratio, the ground dry lithium slag, slag and fly ash are accurately weighed and fully mixed using a mixing device to ensure that the various raw materials are evenly distributed in the admixture. Add an activator to the uniformly mixed raw materials. The activator can be selected from one or more mixtures of silica ash, sodium metasilicate, sodium silicate, and sodium hexametaphosphate. The specific selection and usage amount are determined according to actual needs. After adding the activator, continue to stir fully to ensure that all raw materials and the activator are evenly mixed to form a homogeneous lithium slag-based composite admixture.

[0058] In summary, the lithium slag of this application undergoes the following reactions during the treatment process:

[0059] 2NH4 + +CO3 2- +SO4 2- +Ca 2+ →CaCO3+(NH4)2SO4 ①

[0060] R m+ +(Al-OH-Cl) n+ +SO4 2- →[R(Al-OH-Cl)2(SO4) m+n ↓+R2(SO4) m ] ② Where: R is a metal element, m is the valence, n is the valence of aluminum in polyaluminium chloride. M is a metal element (K, Na, Ca, etc.); and Later, it participates in cement hydration reaction. In the later stage, it can participate in the secondary volcanic ash hydration reaction.

[0061] In the present application, the sulfur content in the lithium slag is reduced by desulfurization, alkali treatment and grinding treatment, the later hydration is promoted, and the dosage in the preparation of composite admixtures is increased. In the present application, before adding the desulfurizer, SO42- is generated by the gypsum reaction in the ammonium salt, so that the sulfur in the gypsum, which is originally insoluble in water, exists in a form that is easier to handle, thereby improving the desulfurization effect. The desulfurized lithium slag is heated and reacted with carbonates to break the bonds of the feldspar minerals in the lithium slag and dissociate to generate products that are beneficial to the hydration of the cementitious material. The pretreated lithium slag is used in conjunction with one or more industrial solid wastes to prepare a composite admixture, so as to realize the resource utilization, high performance and harmless utilization of the lithium slag.

[0062] Table 1: Chemical composition of lithium slag before and after treatment / %

[0063]

[0064]

[0065] In the formed lithium slag-based composite admixture, the mass percentage of the dry lithium slag is 35% to 50%. On the premise of ensuring the strength and durability of the lithium slag-based composite admixture, the proportion of lithium slag is increased, thereby improving the utilization rate of lithium slag, converting industrial waste into valuable building materials, reducing environmental pollution, and realizing the maximum utilization of resources.

[0066] In the second aspect, the embodiment of the present application also provides a lithium slag-based composite admixture, which is made by the preparation method of the lithium slag-based composite admixture described in the first aspect. The lithium slag is pretreated, including reaction with ammonium salts, sulfur reduction, and alkali treatment, so as to reduce the sulfur content in the lithium slag, retain other beneficial components (such as SiO2, Al2O3, CaO, etc.), improve hydration activity, and help increase the amount of lithium slag in the admixture. The pretreated lithium slag is prepared in conjunction with one or more admixtures to prepare a composite admixture, thereby realizing the resource utilization, high performance, and harmless utilization of the lithium slag. Environmental pollution is reduced and waste resource utilization is achieved.

[0067] The following is described by way of examples:

[0068] A lithium slag-based high-activity composite admixture and a preparation method thereof, comprising the following steps:

[0069] After the lithium slag is fully mixed with water, a 5% ammonium salt solution is added, and after sufficient reaction, the mixture is filtered, and 0.5% polyaluminium chloride is added to the filtrate, mixed and stirred, and filtered again, and the secondary filtrate is added to the filter residue, and the above operation is repeated 3 times to obtain the final sulfur reduction filter residue;

[0070] Add 2% sodium carbonate to the desulfurized filter residue, mix and stir, and calcine at 760° C. for 2 hours to obtain dry lithium slag;

[0071] The dried lithium slag and slag are ground to a specific surface area of ​​about 500m2 / kg, and the fly ash is ground to about 380m2 / kg;

[0072] The ground lithium slag, slag and fly ash are mixed in a mass ratio of 2:2:1, and 3% sodium hexametaphosphate is added and mixed evenly to obtain an admixture.

[0073] The obtained admixture was used to prepare mortar test blocks.

[0074] Embodiment 2:

[0075] The steps of the preparation method of the lithium slag-based composite admixture are the same as those of Example 1, except that the mass ratio of lithium slag: slag: fly ash in the raw mineral admixture is 7:8:5.

[0076] Embodiment 3:

[0077] The steps of the preparation method of the lithium slag-based composite admixture are the same as those of Example 1, except that the mass ratio of lithium slag: slag: fly ash in the raw mineral admixture is 9:7:4.

[0078] Embodiment 4:

[0079] The steps of the preparation method of the lithium slag-based composite admixture are the same as those of Example 1, except that the mass ratio of lithium slag: slag: fly ash in the raw mineral admixture is 2:5:3.

[0080] Embodiment 5:

[0081] The steps of the preparation method of the lithium slag-based composite admixture are the same as those of Example 1, except that the mass ratio of lithium slag: slag: fly ash in the raw mineral admixture is 5:3:2.

[0082] Table 2: Mortar test activity index

[0083]

[0084]

[0085] From the above table, we can see that when the lithium slag accounts for 50%, the 7-day compressive strength is 75.5% of the benchmark cement compressive strength, and the 7-day activity index is 75.5% of the benchmark cement; the 28-day compressive strength is 86.9% of the benchmark cement compressive strength, and the 28-day activity index is 87.0% of the benchmark cement, which can meet the relevant requirements. When the lithium slag accounts for 35-45%, the 7-day compressive strength is 89.6-115.6% of the benchmark cement compressive strength, and the 7-day activity index is 107.4-145.3% of the benchmark cement; the 28-day compressive strength is 104.1-140.9% of the benchmark cement compressive strength, and the 28-day activity index is 104.1-141.0% of the benchmark cement, which can have better properties.

[0086] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0087] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A method for preparing a lithium slag-based composite admixture, characterized in that: The method comprises: Mixing lithium slag with water, adding 5% to 8% ammonium salt solution, and separating after sufficient reaction to obtain pre-treated lithium slag and primary filtrate; Adding a desulfurizing agent to the primary filtrate, mixing and stirring, and separating to obtain a secondary filtrate; mixing the secondary filtrate with the pretreated lithium slag to form a mixed liquid; Add 5% to 8% ammonium salt solution to the mixed solution, separate and obtain sulfur-reduced lithium slag after sufficient reaction; The sulfur reduction filter residue and the alkali treatment agent are uniformly mixed and calcined for a preset time to obtain dry lithium slag; The lithium slag, slag and fly ash are ground and dried, and the ground dry lithium slag, slag and fly ash are mixed with an activator in a preset ratio to obtain a lithium slag-based composite admixture.

2. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: In the lithium slag-based composite admixture, the mass percentage content of the dry lithium slag is 35% to 50%.

3. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The step of adding 5% to 8% ammonium salt solution to the mixed solution and separating to obtain sulfur-reduced lithium slag after sufficient reaction comprises: The steps of adding 5% to 8% ammonium salt solution to the mixed solution, and separating to obtain pretreated lithium slag and primary filtrate after sufficient reaction; and repeating the steps of adding desulfurizing agent to the primary filtrate, mixing and stirring, and separating to obtain secondary filtrate 2-5 times; mixing the secondary filtrate with the pretreated lithium slag to form a mixed solution; and adding 5% to 8% ammonium salt solution to the mixed solution; After sufficient reaction, the sulfur-reduced lithium slag is separated.

4. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The desulfurizing agent includes at least one of hydrotalcite, chitosan and polyaluminium chloride.

5. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The alkali treatment agent includes sodium carbonate, calcium carbonate or a mixture thereof.

6. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The ammonium salt solution is a solution of one or more mixtures of ammonium carbonate, ammonium bicarbonate and ammonium chloride.

7. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: In the step of uniformly mixing the sulfur reduction filter residue and the alkali treatment agent and calcining for a preset time, the calcination temperature is 750° C. to 850° C., and the calcination time is 1 to 4 hours.

8. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The specific surface area of ​​the dry lithium slag after grinding is 450-550m2 / kg; the specific surface area of ​​the slag after grinding is 450-550m2 / kg, and the specific surface area of ​​the fly ash after grinding is 300-450m2 / kg.

9. The method for preparing the lithium slag-based composite admixture according to claim 1, characterized in that: The activator is one or more of silica fume, sodium metasilicate, sodium silicate and sodium hexametaphosphate.

10. A lithium slag-based composite admixture, characterized in that: The lithium slag-based composite admixture is prepared by the preparation method of the lithium slag-based composite admixture according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method, application and device of surface modified nano CaCO3 and CaCO3-Fe3O4

    CN120681779A

  • Preparation method, use and device of surface modified nano-CaCO3 and CaCO3@Fe3O4

    CN120681779B